An ethics of enchantment: forming affect and information in experimental paediatric medicine. (3rd January 2022) - Addison, Courtney
Abstract: Science and medicine have been cast as disenchanted arenas of modernity, even as scholars have illustrated the many enchantments of everyday life. Taking these conversations into the context of experimental paediatric medicine, I explore the dis/enchantments produced through the research ethics systems that govern interactions between medical practitioners and patients' families. Research ethics enact forms of disenchantment, aiming to produce the informed patient‐subject who can knowingly submit to the unknowns of experimental medicine. However, by following one young patient's emotive disruption of the consent process, I suggest that we instead consider an ethics of enchantment: one that recognizes the affective logics of patienthood alongside the informatic. Elaborating how ethical practice is both institutionally structured and interpersonally improvised, I develop key conversations from the anthropology of ethics, and highlight the interplay of enchantment and disenchantment that constitutes modern medical subjects. Abstrait: Éthique de l'enchantement : gérer l'effet et l'information dans la médecine pédiatrique expérimentale Résumé La science et la médecine sont considérées comme des lieux désenchantés de la modernité, alors même que des chercheurs ont illustré les nombreux enchantements de la vie quotidienne. En portant ce débat dans le contexte de la médecine pédiatrique expérimentale, l'autrice explore le désenchantement et l'enchantement produits par les systèmes d'éthique de la recherche qui régissent les interactions entre praticiens médicaux et familles de patients. L'éthique de la recherche incarne des formes de désenchantement en cherchant à produire un patient‐sujet informé qui puisse se soumettre en connaissance de cause aux inconnues de la médecine expérimentale. En suivant les perturbations émotionnelles du processus de consentement par un jeune patient, l'autrice suggère qu'il faudrait au contraire envisager une éthique de l'enchantement : une éthique reconnaissant la logique affective de la parentalité en même temps que la logique informative. En exposant comment la pratique éthique est à la fois structurée par l'institution et improvisée entre les personnes, l'article développe des débats cruciaux de l'anthropologie de l'éthique et met en lumière l'interaction entre enchantement et désenchantement qui constitue les sujets médicaux modernes.